Determinants of service quality affecting the customer's satisfaction in department of veterinary service Johor, Johor Bahru / Muhammad Harris Shukor, Ruhil Izzati Rushdi and Nabiha Rosman - Shukor, Muhammad Harris; Rushdi, Ruhil Izzati; Rosman, Nabiha (2022)
Department of Veterinary Services Johor, Johor Bahru had received complaints on their services. However, complaints were vague and unspecific. Researchers decided to adapt the SERVQUAL framework in this study to identify the satisfaction of customers towards DVS Johor, Johor Bahru and may improve on which area that needed to be focus on. This study uses the SWOT (Strength, Weakness, Opportunity and Threats) approach to analyse the issues at Department of Veterinary Services Johor, Johor Bahru. This study aims to investigate the relationship between determinants of service quality with customer's satisfaction. The determinants are Tangibility, Empathy, Reliability, Responsiveness and Assurance. The approach of this study is a quantitative method using a structured questionnaire. A total of 278 questionnaire forms were collected and processed using the statistical tool SPSS to test the hypotheses that had been developed. In this study, researchers found that responsiveness has moderate relationship with customer's satisfaction. Tangibility and assurance have low relationship with customer's satisfaction. Empathy and responsiveness have very low relationship with customer's satisfaction. All null hypotheses are rejected. Therefore, Department of Veterinary Services Johor, Johor Bahru need to improve on the responsiveness factors to cater customer's satisfaction.